2011
DOI: 10.4103/0974-7788.83188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Triphala and Chlorhexidine mouthwash on dental plaque, gingival inflammation, and microbial growth

Abstract: The objective of this study was to ascertain the effects of a mouthwash prepared with Triphala on dental plaque, gingival inflammation, and microbial growth and compare it with commercially available Chlorhexidine mouthwash. This study was conducted after ethics committee approval and written consent from guardians (and assent from the children) were obtained. A total of 1431 students in the age group 8–12 years, belonging to classes fourth to seventh, were the subjects for this study. The Knowledge, Attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 9 publications
7
65
0
1
Order By: Relevance
“…chebula (aqueous extract) strongly inhibited the microbial growth, sucrose induced adherence and glucan induced aggregation of S.mutans. Mouth rinsing with a 10% solution of the extract inhibited microbial count [27]. T. chebula demonstrated preventive action on dental caries has shown that owning to the microbial reduction may be attributed to the presence of tannins and flavonoid [28].…”
Section: Discussionmentioning
confidence: 99%
“…chebula (aqueous extract) strongly inhibited the microbial growth, sucrose induced adherence and glucan induced aggregation of S.mutans. Mouth rinsing with a 10% solution of the extract inhibited microbial count [27]. T. chebula demonstrated preventive action on dental caries has shown that owning to the microbial reduction may be attributed to the presence of tannins and flavonoid [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be used as an adjunct to mechanical therapy for treating plaque induced gingivitis [75,76]. Patel and Ventakrishna reported a significant reduction in probing depth and gain in clinical attachment level by its use [77]. 0.6% triphala mouth wash has been reported to reduce plaque scores, improve gingival health and have an inhibitory effect on bacterial count [77].…”
Section: Maintenance Of Oral Hygienementioning
confidence: 99%
“…Patel and Ventakrishna reported a significant reduction in probing depth and gain in clinical attachment level by its use [77]. 0.6% triphala mouth wash has been reported to reduce plaque scores, improve gingival health and have an inhibitory effect on bacterial count [77]. Triphla is Composed of the fruits of three trees, Indian gooseberry Amalaki (Embilica officinalis), Bibhitaki (Terminalia beleria), and Haritaki (Terminalia chebula), and is mentioned throughout the ancient literature of Ayurvedic medicine as a tonic, highly prized for its ability to regulate the process of digestion and elimination.…”
Section: Maintenance Of Oral Hygienementioning
confidence: 99%
“…The foremost chemical agents currently available are chlorhexidine, triclosan, cetylpyridinium chloride, and natural products [10] [11]. In this respect, natural products have been proposed in attempt to minimize undesirable effects caused by synthetic agents such as imbalance of the resident microbiota, and altered taste, besides representing a new antimicrobial possibility that might be used to face a situation of microbial resistance [12].…”
Section: Introductionmentioning
confidence: 99%